Pengembangan Media Pembelajaran Matematika Berbasis Android Menggunakan Power Point Dan Ispring Suite Pada Materi Persamaan Kuadrat - Wohen, Yulia Avanti Dua; Ekowati, Christine K.; Nubatonis, Ofirenty E. (Universitas Nusa Cendana, 2024)
This research aims to develop mathematics learning media based on an Android application using PowerPoint and I-spring Suite on Quadratic Equations material for class IX students at SMP Negeri 1 Bola that is valid, practical and effective. The method used in this research is Research and Development (R&D) using the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) development model. The research results show that the learning media developed meets the feasibility criteria of being valid, practical and effective. The average total validity by material experts is 4.60 and media experts is 4.57 in the